Anatomical Study of the Horseshoe Kidney - Tijerina de la Garza,Octavio (Sociedad Chilena de Anatomía, 2009)
We present the anatomical study of a horseshoe kidney found during dissection practice at the human anatomy laboratory. The specimen consisted of a renal mass joined at its lower poles by an isthmus composed of renal parenchyma. We provide a macroscopic description of renal blood supply and the excretory system. We also discuss the anatomic and embryologic importance of this anomaly.